An analysis of the impact of soft skills on Malaysian technical institutions - Wan Mohamed, Wan Azlinda; Ibrahimi, Mohammed (American Scientific Publishers, 2017)
Many people recognize the importance of technical skills as knowledge and proficiencies required in the accomplishment of professional jobs. However, the importance and applicability of soft skills are mostly ignored despite the fact that, it is a process how individual carry himself in an organization or professional environment for the progress of that individual and the organization he found himself. The paper explored into some journals from the previous the literatures, some soft skills were identified such as communication, lifelong learning, entrepreneurship, leadership, and teamwork, problem solving and critical among TVET institutions in Malaysia. Document analysis was conducted as a methodology for this study. The impacts of these soft skills on TVET related institutions like polytechnics, training centers and universities in Malaysia. It was indicated that, the result of the impact of soft skills on these institutions was generally moderate. The paper concluded that, technical skills alone could not bring about the organizational development there must be a compliment of soft skills for any organizational sustainability. Supplementary of soft and technical skills conceptual model was formulated. The paper was concluded by saying that, the competitive nature of the present situation, soft skills are essential because they have affected all aspect of human development. Some recommendations were suggested, teachers, lecturers and instructor must teach students soft skills for complete individual proficiencies and organizational sustainability.